Iron-nickel-based high-temperature alloy welding material, preparation method and application thereof
Patent Information
- Application Number
- CN202611205142.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-10
- Publication Date
- 2026-10-30
AI Technical Summary
[0006]本发明的目的是针对目前650℃超超临界电站过热器、再热器等铁镍基高温合金管道无专用配套焊材的问题,基于工程设计要求和系统性研究工作,提出了一种耐高温、长寿命铁镍基高温合金焊材及其制备方法和应用
本发明解决了650℃超超临界燃煤电站过热器、再热器等铁镍基高温合金管道无专用配套焊材的问题。与现有630℃及以下蒸汽温度超超临界电站用的铁基耐热钢焊材相比,本发明的铁镍基高温合金焊材承温能力达到了650℃,满足电站设计要求。与现有镍基高温合金焊材相比,具有成本低、与母材匹配性好、焊接性能好的优势,其成本只有镍基合金Inconel617B、Inconel740H的60~70%,可大规模推广应用,其成分与母材相近,在焊接熔合性、膨胀系数、导热系数等方面与母材匹配度好,焊接性好、可靠性高。在使用的便捷性方面,本发明的焊材在现场焊接后不需要进行固溶热处理,直接进行焊缝的低温时效热处理即可达到性能要求。
Smart Images

Figure CN123000307A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of metallic materials, specifically relating to an iron-nickel-based high-temperature alloy welding material, its preparation method, and its application. Background Technology
[0002] In the field of power energy production, coal-fired power generation is one of the mainstream power production methods, characterized by stable power supply, high reliability, and flexible load regulation, which can effectively ensure the continuous and stable operation of the power system. Adhering to the development of clean, efficient, and flexible high-parameter coal-fired power generating units in building a new energy system with new energy sources as the mainstay is crucial for ensuring the safe and stable operation of the new power system and the energy transition.
[0003] Coal-fired power generation uses high-temperature, high-pressure steam to drive a steam turbine, and the higher the steam temperature and pressure, the higher the power generation efficiency. Currently, the mainstream international coal-fired power generation uses steam pressures of around 27-32 MPa and steam temperatures of 566-620℃, achieving thermal efficiencies of 42-45%, known as ultra-supercritical units (A-USC). The new generation of ultra-high-parameter ultra-supercritical units can achieve a main steam pressure of 35.5 MPa and a steam temperature of 631℃, with a thermal efficiency exceeding 50%, reducing coal consumption for power generation to 256.28 g / kWh, significantly reducing coal consumption per unit of power generation and demonstrating significant energy-saving advantages. Building on this technological iteration, the industry's next step is to focus on 650℃-level ultra-supercritical coal-fired power generation technology as a core research and development direction. By continuously improving steam temperature parameters, further optimizing power generation efficiency, reducing fuel consumption, and promoting the upgrading of coal-fired power generation technology towards high efficiency, low carbon emissions, and energy conservation.
[0004] Superheaters and reheaters are key metal piping components in ultra-supercritical coal-fired power boilers, converting the heat generated from coal combustion into high-temperature, high-pressure steam. These components involve numerous welds, requiring the outer side of the pipes to resist corrosion from coal flue gas and the inner side to resist oxidation corrosion from supercritical water. They must also withstand high temperatures and pressures, making them the most demanding and demanding components in the entire ultra-supercritical system. As steam temperatures continue to increase, the metal materials used are constantly being upgraded. For ultra-supercritical power plants with steam temperatures of 630℃ and below, high-temperature piping components in superheaters and reheaters widely utilize iron-based heat-resistant steels, such as P91 / T91, P92 / T92, and G115. Welded joints generally use welding materials of the same or similar composition. Currently, existing technology has successfully developed iron-nickel-based high-temperature alloy materials for superheaters and reheaters in ultra-supercritical power plants with steam temperatures of 650℃, but there are no dedicated matching welding materials. Existing iron-based heat-resistant steel welding materials used in ultra-supercritical power plants with steam temperatures of 630℃ and below are insufficient to withstand long-term service at 650℃. Although nickel-based superalloy welding materials such as Inconel 617B and Inconel 740H meet the requirement of 650℃ heat resistance, they are dissimilar materials with mismatches in terms of fusion properties, coefficient of expansion, and thermal conductivity, resulting in high welding difficulty, poor reliability, and high price. In the context of a low-cost power market, it is difficult to promote and apply them on a large scale.
[0005] Therefore, it is necessary to develop a high-temperature resistant, long-life iron-nickel-based high-temperature alloy welding material suitable for 650℃ ultra-supercritical coal-fired power plants, mainly used for welding iron-nickel-based high-temperature alloy pipelines such as superheaters and reheaters. Summary of the Invention
[0006] The purpose of this invention is to address the problem that there are no dedicated matching welding materials for iron-nickel-based high-temperature alloy pipelines such as superheaters and reheaters in 650℃ ultra-supercritical power plants. Based on engineering design requirements and systematic research, this invention proposes a high-temperature resistant, long-life iron-nickel-based high-temperature alloy welding material, its preparation method, and its application.
[0007] To achieve the above objectives, the present invention adopts the following technical solution: A nickel-iron-based high-temperature alloy welding material, wherein the composition of the nickel-iron-based high-temperature alloy welding material, by weight percentage, comprises: C 0.01-0.08%, Cr 15-22%, Al 1.0-2.5%, Ti 1.0-2.5%, Mo 2.05-3.0%, Co 1.8-2.3%, B 0.001-0.005%, Fe 25-30%, with the balance including Ni and unavoidable impurities.
[0008] Furthermore, the composition of the iron-nickel-based high-temperature alloy welding material, by weight percentage, includes: C 0.01-0.08%, Cr 16.7-20.88%, Al 1.82-2.0%, Ti 2.04-2.48%, Mo 2.05-3.0%, Co 1.8-2.24%, B 0.001-0.003%, Fe 25-30%, with the balance including Ni and unavoidable impurities.
[0009] Furthermore, the weight percentages of Al, Ti, and Co in the iron-nickel-based high-temperature alloy welding material satisfy the following relationships: 1.05 ≤ Ti / Al ≤ 1.6, 4.3% ≤ Al + Ti + Co ≤ 6.7%.
[0010] Furthermore, the weight percentages of Al, Ti, and Co in the iron-nickel-based high-temperature alloy welding material satisfy the following relationships: 1.09 ≤ Ti / Al ≤ 1.27, 5.7% ≤ Al + Ti + Co ≤ 6.52%.
[0011] Furthermore, the unavoidable impurities have a weight percentage content of ≤0.5%.
[0012] Furthermore, the unavoidable impurities, by weight percentage, include: W ≤ 0.10%; and / or, Si ≤ 0.10%; and / or, Mn ≤ 0.10%; and / or, P ≤ 0.008%; and / or, S ≤ 0.005%; and / or, Nb ≤ 0.10%; and / or, Cu ≤ 0.10%; and / or, Pb ≤ 0.001%; and / or, Sn ≤ 0.001%; and / or, As ≤ 0.001%; and / or, Sb ≤ 0.001%; and / or, Bi ≤ 0.0005%.
[0013] Furthermore, the microstructure of the iron-nickel-based high-temperature alloy welding material is deformed austenite plus carbides.
[0014] A method for preparing an iron-nickel-based high-temperature alloy welding material includes the following steps: S1. Take raw materials according to the alloy welding material composition ratio, melt them in a vacuum environment, refine and degas them after the raw materials are completely melted, and vacuum cast them into electrode rods. S2. Vacuum remelting is performed on the electrode rod described in S1 to prepare an alloy ingot; S3. Perform diffusion annealing on the alloy ingot described in S2; S4. The annealed alloy ingot is forged into a billet and then hot-rolled to obtain wire rod. S5. Anneal and soften the wire rod described in S4, and then peel it. After peeling, the wire rod is drawn, annealed and cleaned in multiple passes to obtain the finished welding wire.
[0015] Furthermore, in step S3, the diffusion annealing temperature of the alloy ingot is 1180-1200℃, and the annealing time is 24-48h; in step S5, the wire rod annealing and softening process is carried out at 1050-1080℃ for 1-3h, which is used to refine the internal grains of the alloy, reduce the hardness of the wire rod, and adapt to the subsequent drawing process.
[0016] An application of an iron-nickel-based high-temperature alloy welding material, wherein the iron-nickel-based high-temperature alloy welding material is used to manufacture piping components for ultra-supercritical units.
[0017] Compared with the prior art, the present invention has the following beneficial effects: This invention solves the problem of the lack of dedicated welding materials for iron-nickel-based high-temperature alloy pipelines in superheaters and reheaters of 650℃ ultra-supercritical coal-fired power plants. Compared with existing iron-based heat-resistant steel welding materials used in ultra-supercritical power plants with steam temperatures of 630℃ and below, the iron-nickel-based high-temperature alloy welding material of this invention has a temperature resistance capacity of 650℃, meeting the design requirements of the power plant. Compared with existing nickel-based high-temperature alloy welding materials, it has the advantages of low cost, good compatibility with the base material, and good welding performance. Its cost is only 60-70% of that of nickel-based alloys Inconel 617B and Inconel 740H, which can be widely used. Its composition is similar to that of the base material, and it has good compatibility with the base material in terms of weld fusion, coefficient of expansion, and thermal conductivity, resulting in good weldability and high reliability. In terms of ease of use, the welding material of this invention does not require solution heat treatment after on-site welding; it can directly achieve the performance requirements through low-temperature aging heat treatment of the weld.
[0018] This invention, by strictly controlling the carbon content in the alloy welding material, improves the fluidity of the liquid metal during welding and facilitates the formation of M23C6 and other carbides along grain boundaries during heat treatment. This strengthens the grain boundaries, delaying the initiation, expansion, and merging of creep cavities, thereby improving the high-temperature creep life of the alloy. When the carbon content is less than 0.01%, it is insufficient to form a sufficient number of M23C6. When the carbon content is too high, the resulting M23C6 carbides are larger and consume excessive amounts of Mo, Cr, and Ti in the alloy. This not only reduces the solid solution strengthening effect of Mo and Cr but also reduces the Al and Ti available for forming the Ni3 (Al, Ti) strengthening phase, negatively impacting the high-temperature strength and creep performance of the alloy.
[0019] This invention improves the alloy's oxidation resistance, water vapor oxidation resistance, and corrosion resistance, especially its sulfur corrosion resistance, by using an appropriate amount of Cr. Considering the requirements for resistance to supercritical water vapor oxidation corrosion at 650℃ and flue gas corrosion, the Cr content needs to be controlled above 15%. However, excessively high Cr content easily leads to the formation of Top-packed close-packed phases, reducing the long-term microstructure stability of the alloy. This invention balances oxidation resistance, corrosion resistance, and long-term microstructure stability, controlling the Cr content at 15-22%. Mo is an important solid solution strengthening element and a carbide-forming element. Finely dispersed Mo carbides greatly promote the high-temperature strength and creep resistance of the alloy. However, excessive Mo content can easily lead to harmful TCP phase. Through systematic research, this invention shows that when the Mo content does not exceed 2%, Mo carbides on the grain boundaries are not obvious. When the Mo content is between 2.05% and 3.0%, a considerable number of Mo carbides can be formed at the grain boundaries. However, when the Mo content is higher than 3%, harmful TCP phase is easily formed during long-term service at 650°C. Therefore, the Mo content in this invention is controlled at 2.05% to 3.0%, and the W content should be controlled to not exceed 0.1%.
[0020] In this invention, the role of Co itself and its interaction with Al and Ti are considered, and the Co content is controlled at 1.8~2.3%, with 4.3%≤Al+Ti+Co≤6.7%. Co is both an important solid solution strengthening element and an important precipitation strengthening element. Co can dissolve in the matrix to provide good solid solution strengthening effect for the alloy, significantly reduce the stacking fault energy of the matrix, widen the dislocation width, and make dislocations less prone to clustering and cross-slip, thereby improving the creep resistance and service life of the alloy. Co can also partially replace elements in the Ni3Al type precipitate strengthening phase, improving the stability of the phase during long-term service; Co can also reduce the solid solubility of Al and Ti in the matrix, promote the precipitation of γ′ strengthening phase and increase its precipitation quantity and solid solution temperature.
[0021] The appropriate addition of boron (B) in this invention serves two purposes: first, B has a very small atomic radius of approximately 85 picometers, while Ni has an atomic radius of approximately 135 picometers. Therefore, B atoms easily accumulate at grain boundaries, preventing harmful low-melting-point elements from segregating there, thus improving grain boundary bonding. Second, borides at grain boundaries can inhibit grain boundary slip, void initiation, and propagation, which is beneficial for improving the alloy's creep resistance and service life. However, excessive B will deteriorate the alloy's weldability; therefore, the B content should be controlled at 0.001-0.005%.
[0022] In this invention, the appropriate addition of Fe to replace Ni can not only reduce the cost of the alloy, but also improve its hot workability. However, excessive Fe content will reduce the alloy's corrosion resistance, hinder the precipitation of the strengthening phase γ′, and reduce the alloy's microstructure stability and high-temperature strength. The Fe content of the alloy in this invention is controlled at 25-30%.
[0023] In this invention, both Ti and Al are γ′ phase forming elements. The precipitated γ′ phase can promote the high-temperature strength of the alloy, and Al also improves the alloy's resistance to internal oxidation. However, excessive content affects weldability. Ti has the effect of resisting heat and sulfide corrosion, but excessive content can easily form the harmful TCP phase. Simultaneously, the Ti / Al ratio also affects the alloy's microstructure and properties. Excessive Ti / Al ratio reduces the stability of the γ′ phase at high temperatures, causing phase transformation and reducing the alloy's high-temperature strength and hot workability. Insufficient Ti / Al ratio results in lower alloy strength and plasticity. Considering both the alloy's strength and microstructure stability, the Ti content is controlled at 1.0~2.5%, Al at 1.0~2.5%, and 1.05≤Ti / Al≤1.6.
[0024] In this invention, the Si content is controlled to be less than or equal to 0.10%. Si is an important deoxidizing element, and its appropriate addition can promote the oxidation resistance of the alloy. However, excessive Si content will reduce the weldability of the alloy. Mn can replace Ni to form and stabilize austenite and has the function of fixing S in the alloy. However, excessive Mn content will reduce the oxidation resistance of the alloy. The Mn content is controlled to be less than or equal to 0.10%. Nb is a strengthening element for the γ′ phase. Its addition can promote the high-temperature strength of the alloy. However, it is prone to forming large-sized NbC in the liquid metal during the welding process and inducing cracks. The Nb content is controlled to be no more than 0.10%. Cu can promote and stabilize the precipitation of the γ′ phase and improve the corrosion resistance to non-oxidizing acids. However, excessive Cu will reduce the high-temperature strength of the alloy. The Cu content is controlled to be less than or equal to 0.10%. Attached Figure Description
[0025] Figure 1 The microstructure of the weld metal prepared in Example 1 of this invention is shown. Figure 2 This refers to the grain boundary carbide of the weld metal prepared in Example 1 of the present invention. Detailed Implementation
[0026] The following specific examples illustrate the implementation of the present invention. Those skilled in the art can easily understand other advantages and effects of the present invention from the content disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and various details in this specification can also be modified or changed based on different viewpoints and applications without departing from the spirit of the present invention.
[0027] It should be noted that the process equipment or apparatus not specifically mentioned in the following embodiments are all conventional equipment or apparatus in the art.
[0028] It should be noted that the terms "comprising" and "having," and any variations thereof, are intended to cover non-exclusive inclusion. For example, a process, method, system, product, or apparatus that includes a series of steps or units is not necessarily limited to those steps or units explicitly listed, but may include other steps or units not explicitly listed or inherent to these processes, methods, products, or apparatuses. Furthermore, unless otherwise stated, the numbering of each method step is merely a convenient tool for identifying each method step, and not intended to limit the order of the method steps or define the scope of the invention. Changes or adjustments to their relative relationships, without substantially altering the technical content, should also be considered within the scope of the invention.
[0029] The purpose of this invention is to address the current lack of dedicated welding materials for iron-nickel-based high-temperature alloy pipelines in superheaters and reheaters of 650℃ ultra-supercritical power plants. Based on engineering design requirements and systematic research, this invention proposes a high-temperature resistant, long-life iron-nickel-based high-temperature alloy welding material and its preparation method. Specific engineering design indicators are: the welding material composition system must be an iron-nickel-based high-temperature alloy, possessing good weldability, free from welding cracks, and after post-weld aging heat treatment at 800℃ for 4~10h, the deposited metal properties are: room temperature tensile strength Rp0.2≥471MPa, Rm≥855MPa; 650℃ high-temperature tensile strength Rp0.2≥500MPa, Rm≥782MPa; and creep rupture life ≥115 hours under 650℃ / 425MPa conditions. Existing iron-nickel-based high-temperature alloys cannot simultaneously meet these comprehensive requirements.
[0030] The present invention discloses an iron-nickel-based high-temperature alloy welding material, wherein the composition of the iron-nickel-based high-temperature alloy welding material, by weight percentage, comprises: C 0.01-0.08%, Cr 15-22%, Al 1.0-2.5%, Ti 1.0-2.5%, Mo 2.05-3.0%, Co 1.8-2.3%, B 0.001-0.005%, Fe 25-30%, with the balance including Ni and unavoidable impurities.
[0031] In a preferred embodiment of the present invention, the composition of the iron-nickel-based high-temperature alloy welding material, by weight percentage, includes: C 0.01-0.08%, Cr 16.7-20.88%, Al 1.82-2.0%, Ti 2.04-2.48%, Mo 2.05-3.0%, Co 1.8-2.24%, B 0.001-0.003%, Fe 25-30%, with the balance including Ni and unavoidable impurities.
[0032] In a preferred embodiment of the present invention, the weight percentages of Al, Ti, and Co in the iron-nickel-based high-temperature alloy welding material satisfy the following relationships: 1.05 ≤ Ti / Al ≤ 1.6, 4.3% ≤ Al + Ti + Co ≤ 6.7%.
[0033] In a preferred embodiment of the present invention, the weight percentages of Al, Ti, and Co in the iron-nickel-based high-temperature alloy welding material satisfy the following relationships: 1.09 ≤ Ti / Al ≤ 1.27, 5.7% ≤ Al + Ti + Co ≤ 6.52%.
[0034] In a preferred embodiment of the present invention, the unavoidable impurities have a weight percentage content of ≤0.5%.
[0035] In a preferred embodiment of the present invention, the unavoidable impurities comprise, by weight percentage: W ≤ 0.10%; and / or, Si ≤ 0.10%; and / or, Mn ≤ 0.10%; and / or, P ≤ 0.008%; and / or, S ≤ 0.005%; and / or, Nb ≤ 0.10%; and / or, Cu ≤ 0.10%; and / or, Pb ≤ 0.001%; and / or, Sn ≤ 0.001%; and / or, As ≤ 0.001%; and / or, Sb ≤ 0.001%; and / or, Bi ≤ 0.0005%.
[0036] In a preferred embodiment of the present invention, the microstructure of the iron-nickel-based high-temperature alloy welding material is deformed austenite plus carbides.
[0037] A method for preparing an iron-nickel-based high-temperature alloy welding material includes the following steps: S1. Take raw materials according to the alloy welding material composition ratio, melt them in a vacuum environment, refine and degas them after the raw materials are completely melted, and vacuum cast them into electrode rods, preferably electrode rods with a diameter of Φ220mm. S2. The electrode rod described in S1 is vacuum remelted to prepare an alloy ingot, preferably an alloy ingot with a diameter of Φ280-Φ320mm; S3. Perform diffusion annealing on the alloy ingot described in S2; preferably, the annealing temperature is 1180-1200℃ and the annealing time is 24-48h. S4. Forge the annealed alloy ingot into a square billet, preferably with a cross-sectional side length of 80-120mm; hot roll the square billet into wire rod, preferably with a diameter of Φ8mm. S5. Anneal and soften the wire rod described in S4, preferably at 1050-1080℃ for 1-3 hours, to refine the internal grains of the alloy, reduce the hardness of the wire rod, and adapt to the subsequent drawing process; then peeling is performed, and the peeled wire rod is drawn, annealed, and cleaned in multiple passes to obtain the finished welding wire.
[0038] An application of an iron-nickel-based high-temperature alloy welding material, wherein the iron-nickel-based high-temperature alloy welding material is used to manufacture piping components for ultra-supercritical units.
[0039] Example 1 The alloy welding material of this embodiment has the following composition by weight percentage: C 0.044%, Cr 20.88%, Al 1.82%, Ti 2.48%, Mo 2.05%, Co 2.0%, B 0.002%, Fe 27.67%, with the balance being Ni.
[0040] The alloy welding material of this embodiment is prepared by the following steps: Selected raw materials with the required purity were weighed according to the design ratio and placed in a vacuum induction melting furnace for melting under vacuum conditions. After all the raw materials were melted, a vacuum of 0.1-0.5 Pa was maintained for 30-35 minutes to remove gases. After refining, the materials were cast into electrode rods with a diameter of Φ220 mm under vacuum conditions. After vacuum self-consumption remelting, alloy ingots with a diameter of 280 mm were obtained. The alloy ingots were then subjected to diffusion annealing at 1180℃ for 40 hours. The alloy ingots were forged at 1100℃ and forged into 85×85 mm square billets through three heat treatments, and then rolled into Φ8 mm wire rods through two heat treatments. The wire rods were annealed and softened at 1050℃ for 1 hour, then peeled, and after multiple draws, annealing, and cleaning, they were made into welding wires of the required specifications. The composition of the alloy welding material prepared in Example 1 is shown in Table 1, and the properties are shown in Table 2.
[0041] Example 2 The alloy welding material of this embodiment has the following composition by weight percentage: C 0.01%, Cr 19.25%, Al 1.95%, Ti 2.30%, Mo 2.12%, Co 1.82%, B 0.002%, Fe 25.6%, with the balance being Ni.
[0042] The alloy welding material of this embodiment is prepared by the same method as that of Example 1, except that the alloy composition ratio is different.
[0043] Example 3 The alloy welding material of this embodiment has the following composition by weight percentage: C 0.08%, Cr 18.56%, Al 1.9%, Ti 2.32%, Mo 2.25%, Co 2.30%, B 0.003%, Fe 29.8%, with the balance being Ni.
[0044] The alloy welding material of this embodiment is prepared by the same method as that of Example 1, except that the alloy composition ratio is different.
[0045] Example 4 The alloy welding material of this embodiment has the following composition by weight percentage: C 0.06%, Cr 22.0%, Al 1.85%, Ti 2.05%, Mo 2.36%, Co 1.80%, B 0.002%, Fe 30.0%, with the balance being Ni.
[0046] The alloy welding material of this embodiment is prepared by the same method as that of Example 1, except that the alloy composition ratio is different.
[0047] Example 5 The alloy welding material of this embodiment has the following composition by weight percentage: C 0.05%, Cr 21.5%, Al 1.88%, Ti 2.10%, Mo 2.43%, Co 2.12%, B 0.002%, Fe 25.0%, with the balance being Ni.
[0048] The alloy welding material of this embodiment is prepared by the same method as that of Example 1, except that the alloy composition ratio is different.
[0049] Example 6 The alloy welding material of this embodiment has the following composition by weight percentage: C 0.07%, Cr 19.8%, Al 1.89%, Ti 2.08%, Mo 3.0%, Co 2.23%, B 0.003%, Fe 27.0%, with the balance being Ni.
[0050] The alloy welding material of this embodiment is prepared by the same method as that of Example 1, except that the alloy composition ratio is different.
[0051] Example 7 The alloy welding material of this embodiment has the following composition by weight percentage: C 0.045%, Cr 18.4%, Al 1.82%, Ti 2.32%, Mo 2.98%, Co 2.24%, B 0.002%, Fe 28.2%, with the balance being Ni.
[0052] The alloy welding material of this embodiment is prepared by the same method as that of Example 1, except that the alloy composition ratio is different.
[0053] Example 8 The alloy welding material of this embodiment has the following composition by weight percentage: C 0.065%, Cr 16.7%, Al 1.93%, Ti 2.23%, Mo 2.70%, Co 2.10%, B 0.003%, Fe 27.6%, with the balance being Ni.
[0054] The alloy welding material of this embodiment is prepared by the same method as that of Example 1, except that the alloy composition ratio is different.
[0055] Example 9 The alloy welding material of this embodiment has the following composition by weight percentage: C 0.048%, Cr 16.9%, Al 2.0%, Ti 2.18%, Mo 2.65%, Co 2.05%, B 0.002%, Fe 25.4%, with the balance being Ni.
[0056] The alloy welding material of this embodiment is prepared by the same method as that of Example 1, except that the alloy composition ratio is different.
[0057] Example 10 The alloy welding material of this embodiment has the following composition by weight percentage: C 0.049%, Cr 20.0%, Al 1.86%, Ti 2.15%, Mo 2.56%, Co 2.03%, B 0.001%, Fe 30%, with the balance being Ni.
[0058] The alloy welding material of this embodiment is prepared by the same method as that of Example 1, except that the alloy composition ratio is different.
[0059] Example 11 The alloy welding material of this embodiment has the following composition by weight percentage: C 0.045%, Cr 15%, Al 1.0%, Ti 1.0%, Mo 2.53%, Co 2.3%, B 0.005%, Fe 30%, with the balance being Ni.
[0060] The alloy welding material of this embodiment is prepared by the same method as that of Example 1, except that the alloy composition ratio is different.
[0061] Example 12 The alloy welding material of this embodiment has the following composition by weight percentage: C 0.04%, Cr 18%, Al 2.0%, Ti 2.5%, Mo 2.10%, Co 2.0%, B 0.003%, Fe 29%, with the balance being Ni.
[0062] The alloy welding material of this embodiment is prepared by the same method as that of Example 1, except that the alloy composition ratio is different.
[0063] Comparative Example 1 The preparation method of Comparative Example 1 is the same as that of Example 1. Comparative Example 1 is the composition of the invention with application number 201210513438.0, which is also the base material composition corresponding to the welding material in this invention. Its Mo content is 0.52%, Ti / Al is 0.95, and the sum of the mass percentages of Al, Ti and Co is Al+Ti+Co=4.47%. The specific alloy composition obtained by Comparative Example 1 is shown in Table 1, and the properties are shown in Table 2.
[0064] Comparative Example 2 Comparative Example 2 was prepared using the same method as Example 1, with a Co content of 0.09%, Ti / Al = 0.96, and the sum of the mass percentages of Al, Ti, and Co was Al + Ti + Co = 4.79%. The specific composition of the alloy obtained in Comparative Example 2 is shown in Table 1, and its properties are shown in Table 2.
[0065] Comparative Example 3 Comparative Example 3 was prepared using the same method as Example 1, with a Co content of 0.10%, Ti / Al = 0.32, and the sum of the mass percentages of Al, Ti, and Co was Al + Ti + Co = 3.37%. The specific composition of the alloy obtained in Comparative Example 3 is shown in Table 1, and its properties are shown in Table 2.
[0066] Comparative Example 4 Comparative Example 4 was prepared using the same method as Example 1, with a Co content of 0.09% and a total mass percentage of Al, Ti, and Co of 1.79%. The specific composition of the alloy obtained in Comparative Example 4 is shown in Table 1, and its properties are shown in Table 2.
[0067] Comparative Example 5 Comparative Example 5 was prepared using the same method as Example 1, with a Co content of 0.08% and a total mass percentage of Al, Ti, and Co of 1.78%. The specific composition of the alloy obtained in Comparative Example 5 is shown in Table 1, and its properties are shown in Table 2.
[0068] Comparative Example 6 Comparative Example 6 was prepared using the same method as Example 1, with a Co content of 0.09%, a Mo content of 3.1%, and a total mass percentage of Al, Ti, and Co of 3.77%. The alloy composition of Comparative Example 6 is shown in Table 1, and its properties are shown in Table 2.
[0069] Comparative Example 7 Comparative Example 7 was prepared using the same method as Example 1, with a Mo content of 3.2%. The alloy composition of Comparative Example 7 is shown in Table 1, and its properties are shown in Table 2.
[0070] Comparative Example 8 Comparative Example 8 was prepared using the same method as Example 1, with a Co content of 3.0% and no Mo added. The sum of the mass percentages of Al, Ti, and Co was Al+Ti+Co=6.9%. The alloy composition of Comparative Example 8 is shown in Table 1, and its properties are shown in Table 2.
[0071] Comparative Example 9 Comparative Example 9 was prepared using the same method as Example 1, with a Co content of 1.6% and a Ti / Al ratio of 0.95. The alloy composition of Comparative Example 9 is shown in Table 1, and its properties are shown in Table 2.
[0072] Comparative Example 10 Comparative Example 10 was prepared using the same method as Example 1, with a Co content of 0.8% and a Ti / Al ratio of 0.87. The alloy composition of Comparative Example 10 is shown in Table 1, and its properties are shown in Table 2.
[0073] Table 1 shows the chemical composition of Examples 1-12 and Comparative Examples 1-10.
[0074] Note: The content of each element in the table is expressed in wt%.
[0075] Table 2 shows the performance comparison between Examples 1-12 and Comparative Examples 1-10.
[0076] Note: 1. The mechanical properties in the table correspond to the weld metal in the aged state. The creep life test conditions are 650℃ / 425MPa; 2. The detection conditions for weld cracks are: according to the national energy industry standard NB / T 47013.5-2015, the surface quality of the weld of 5mm plate is detected by fluorescent penetrant and dye penetrant methods; according to the national standard GB / T 3323.1-2019, the internal quality of the weld of 5mm plate is detected by X-ray. Rp0.2 is the yield strength and Rm is the tensile strength.
[0077] As can be seen from the alloy composition and performance data of each embodiment and comparative example in Tables 1 and 2, in Examples 1-12, all elements are within the scope of the present invention, and the mass percentage content of elements Al, Ti and Co satisfies the following relationship: 1.05≤Ti / Al≤1.6, 4.3%≤Al+Ti+Co≤6.7%. The creep rupture life under the conditions of 650℃ / 425MPa all reached more than 115h, the room temperature strength and the high temperature strength at 650℃ were both qualified, and no welding cracks were generated during the welding process.
[0078] Comparative Example 1 uses the composition from the invention with application number 201210513438.0, which is also the base material composition corresponding to the welding material in this invention. Its Mo content is 0.52%, and the Ti / Al ratio is 0.95. Although the room temperature strength and 650°C high temperature strength of the deposited metal meet the requirements, its creep rupture life is only 16.4 hours, significantly lower than expected. Although the properties of the deformable alloy corresponding to the base material composition meet the requirements, once used as a welding material, the creep rupture life of the deposited metal is significantly reduced, falling far below the design requirements.
[0079] Although Comparative Example 2 increased the Mo content to 2.08% and the Ti / Al ratio to 0.96, it did not add B, resulting in a creep life of only 18.8h, significantly lower than the expected value of 115h, and weld cracks were also generated.
[0080] The Ti / Al ratio of Comparative Example 3 was 0.32, which was lower than the design requirement of this invention, and the Ti content was low, only 0.8%, with Al+Ti+Co=3.37%. Although the creep rupture life was 232h, the strength at room temperature and 650℃ was relatively low. Moreover, due to the high B content of 0.008%, welding cracks occurred.
[0081] The Al, Ti, and Al+Ti+Co contents of Comparative Example 4 were all lower than the design requirements of this invention. Although the service life reached 230h, the strength at room temperature and 650℃ was relatively low due to the insufficient content of the reinforcing elements Al, Ti, and Co.
[0082] The Al, Ti, and Al+Ti+Co contents of Comparative Example 5 were all lower than the design requirements of this invention, and no B element beneficial to grain boundary strengthening was added. The creep life was only 19.6h, and the strength at room temperature and 650℃ was also relatively low.
[0083] The Al+Ti+Co content of Comparative Example 6 was lower than the design requirements of this invention, while the Mo content was higher than the design requirements of this invention. The strength at room temperature and high temperature of 650℃ was relatively low, and the service life was 102h, which was lower than the expected value.
[0084] Comparative Example 7 had a Mo content higher than the design requirements of this invention, resulting in a creep rupture life of only 105 hours, lower than the expected value. Comparative Examples 8-10 all had Mo contents lower than the design requirements of this invention, and their creep rupture lives did not reach 115 hours. This indicates that the effect of Mo content on creep rupture life is two-sided, and there exists an optimal content range. Furthermore, due to the high B content (0.007%) in Comparative Example 9, welding cracks occurred.
[0085] Figure 1 The microstructure of the deposited metal under an electron microscope shows obvious cellular structure characteristics; Figure 2 The image shows the magnified morphological features of the grain boundaries of the deposited metal under an electron microscope, with fine granular carbides distributed along the grain boundaries.
[0086] This invention solves the problem of the lack of dedicated welding materials for iron-nickel-based high-temperature alloy pipelines in superheaters and reheaters of 650℃ ultra-supercritical coal-fired power plants. Compared with existing iron-based heat-resistant steel welding materials used in ultra-supercritical power plants with steam temperatures of 630℃ and below, the iron-nickel-based high-temperature alloy welding material of this invention has a temperature resistance capacity of 650℃, meeting the design requirements of the power plant. Compared with existing nickel-based high-temperature alloy welding materials, it has the advantages of low cost, good compatibility with the base material, and good welding performance. Its cost is only 60-70% of that of nickel-based alloys Inconel 617B and Inconel 740H, which can be widely used. Its composition is similar to that of the base material, and it has good compatibility with the base material in terms of weld fusion, coefficient of expansion, and thermal conductivity, resulting in good weldability and high reliability. In terms of ease of use, the welding material of this invention does not require solution heat treatment after on-site welding; it can directly achieve the performance requirements through low-temperature aging heat treatment of the weld.
[0087] The above embodiments are merely specific implementations of the present invention, used to illustrate the technical solutions of the present invention, and are not intended to limit it. The scope of protection of the present invention is not limited thereto. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that any person skilled in the art can still modify or easily conceive of changes to the technical solutions described in the foregoing embodiments within the scope of the technology disclosed in the present invention, or make equivalent substitutions for some of the technical features; and these modifications, changes, or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention, and should all be covered within the scope of protection of the present invention.
Claims
1. A type of iron-nickel-based high-temperature alloy welding material, characterized in that, The composition of the iron-nickel-based high-temperature alloy welding material, by weight percentage, includes: C 0.01-0.08%, Cr 15-22%, Al 1.0-2.5%, Ti 1.0-2.5%, Mo 2.05-3.0%, Co 1.8-2.3%, B 0.001-0.005%, Fe 25-30%, with the balance including Ni and unavoidable impurities.
2. The iron-nickel-based high-temperature alloy welding material according to claim 1, characterized in that, The composition of the iron-nickel-based high-temperature alloy welding material, by weight percentage, includes: C 0.01-0.08%, Cr 16.7-20.88%, Al 1.82-2.0%, Ti 2.04-2.48%, Mo 2.05-3.0%, Co 1.8-2.24%, B 0.001-0.003%, Fe 25-30%, with the balance including Ni and unavoidable impurities.
3. The iron-nickel-based high-temperature alloy welding material according to claim 1, characterized in that, The weight percentages of Al, Ti, and Co in the iron-nickel-based high-temperature alloy welding material satisfy the following relationship: 1.05≤Ti / Al≤1.6, 4.3%≤Al+Ti+Co≤6.7%.
4. The iron-nickel-based high-temperature alloy welding material according to claim 3, characterized in that, The weight percentages of Al, Ti, and Co in the iron-nickel-based high-temperature alloy welding material satisfy the following formulas: 1.09 ≤ Ti / Al ≤ 1.27, 5.7% ≤ Al + Ti + Co ≤ 6.52%.
5. The iron-nickel-based high-temperature alloy welding material according to claim 1, characterized in that, The unavoidable impurities have a weight percentage content of ≤0.5%.
6. The iron-nickel-based high-temperature alloy welding material according to claim 5, characterized in that, The unavoidable impurities, by weight percentage, include: W ≤ 0.10%; and / or, Si ≤ 0.10%; and / or, Mn ≤ 0.10%; and / or, P ≤ 0.008%; and / or, S ≤ 0.005%; and / or, Nb ≤ 0.10%; and / or, Cu ≤ 0.10%; and / or, Pb ≤ 0.001%; and / or, Sn ≤ 0.001%; and / or, As ≤ 0.001%; and / or, Sb ≤ 0.001%; and / or, Bi ≤ 0.0005%.
7. The iron-nickel-based high-temperature alloy welding material according to claim 1, characterized in that, The microstructure of the iron-nickel-based high-temperature alloy welding material is deformed austenite plus carbides.
8. A method for preparing an iron-nickel-based high-temperature alloy welding material according to any one of claims 1-7, characterized in that, Includes the following steps: S1. Take raw materials according to the alloy welding material composition ratio, melt them in a vacuum environment, refine and degas them after the raw materials are completely melted, and vacuum cast them into electrode rods. S2. Vacuum remelting is performed on the electrode rod described in S1 to prepare an alloy ingot; S3. Perform diffusion annealing on the alloy ingot described in S2; S4. The annealed alloy ingot is forged into a billet and then hot-rolled to obtain wire rod. S5. Anneal and soften the wire rod described in S4, and then peel it. After peeling, the wire rod is drawn, annealed and cleaned in multiple passes to obtain the finished welding wire.
9. The method for preparing an iron-nickel-based high-temperature alloy welding material according to claim 8, characterized in that, The diffusion annealing temperature of the alloy ingot in step S3 is 1180-1200℃, and the annealing time is 24-48h. The wire rod annealing and softening process in step S5 is annealing and softening at 1050-1080℃ for 1-3h, which is used to refine the internal grains of the alloy, reduce the hardness of the wire rod, and adapt to the subsequent drawing process.
10. An application of the iron-nickel-based high-temperature alloy welding material according to any one of claims 1-7, characterized in that, The iron-nickel-based high-temperature alloy welding material is used to manufacture pipeline components for ultra-supercritical units.
Citation Information
Patent Citations
High-strength and corrosion-resistant nickel-iron-chromium-based high-temperature alloy and preparation method for same
CN102994809B
